Національний ботанічний сад ім. М.М. Гришка НАН України: основні результати наукової діяльності - Moroz, P.A.; Gaponenko, М.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
The history of creation and development of the National Botanical Gardens, their structure, principles of laying out, plots and collections are reviewed. Principal scientific achievements in the field of plant introduction and landscape architecture, space biology, allelopathy medical botany and bioindication are presented.